We Didn’t Know: Art, Protest, and Testimony in Argentina during the Dictatorship - Tal-Sultan (1967-2023), Ronit (Mabatim: Journal of Visual Culture, 2024)
This article focuses on the series of artworks titled We Didn’t Know (Nosotros No Sabíamos) created by the Argentinian artist Leon Ferrari referring to the military dictatorship in Argentina. Ferrari’s work, which includes press clippings and missing persons advertisements, serves to reveal, criticize, and protest against the severe violence that took place in his country, which resulted in the disappearance and murder of about 30,000 innocent civilians. Through a visual and theoretical analysis of Ferari’s series, this article offers a new formulation of the role of protest artists as witnesses, art as documentation, and artistic practice as a means of disseminating information and forming collective memory. In this way, the article contributes to contemporary artistic discourse regarding art as testimony and reveals the limits of artistic freedom in times of dictatorships.